WHEN THE CURE BITES BACK: A CASE REPORT ON CARBIMAZOLE-INDUCED MYOSITIS - Menon, Saieehwaran; Ooi, Xin Yi; Lim, Sue Wen; Wong, Hui Chin; Yong, Sy Liang (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Musculoskeletal complaints, including myositis, are common in thyroid disorders. However, it is a rare and non-classical side effect of antithyroid drugs. CASE A 35-year-old male with Graves’ disease was admitted for symptomatic thyrotoxicosis despite treatment with high-dose carbimazole, lithium and dexamethasone for direct observed therapy (DOTS). On examination, he exhibited signs of thyrotoxicosis, including tremors, sweaty palms, proptosis and a large goitre. Thyroid function tests revealed overt thyrotoxicosis (TSH <0.001 mIU/L, T4 122.5 pmol/L). He responded well to DOTS on the same treatment, with T4 decreasing to 27 pmol/L by Day 10 of admission. However, he developed severe proximal muscle aches on day 10. Laboratory investigation revealed an elevated creatinine kinase (CK) level of 5662 IU/L. A diagnosis of carbimazole-induced myositis was made, prompting the discontinuation of carbimazole and initiation of intravenous hydration and cholestyramine while continuing lithium and steroids. The myositis improved, but there was a rebound in his thyrotoxicosis (T4 52 pmol/L), prompting a trial of propylthiouracil, which led to a flare of the myositis (CK 1328 IU/L). He was planned for urgent total thyroidectomy then and was started on Lugol’s iodine. Myalgia and elevated CK levels are rare but recognised manifestations of hyperthyroidism. These can be due to direct effects of thyrotoxicosis on skeletal muscle, thyrotoxic hypokalemic periodic paralysis and drug-induced myositis by carbimazole and propylthiouracil. The pathophysiology of drug-induced myositis may be due to the abrupt decrease in circulating thyroid hormones, leading to a relative hypothyroid state in the peripheral tissues and resulting in myositis. Thioamides may also have a direct toxic effect on myocytes and trigger a local immune response at myocytes, leading to myositis. CONCLUSION This case highlights myositis as a rare side effect of anti-thyroid drugs and can cause significant morbidity. Early recognition and close monitoring are essential for managing this condition.